Marxismo althusseriano y psicoanálisis lacaniano ante la psicología del capitalismo neoliberal: una lectura sintomal - López Ríos, Luis Pablo (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
In the context of the growing psychologization of economics and politics, this work proposes elucidating the relationship between neoliberal capitalism and psychology through a Marxist and Lacanian critique. This work is based on the critique of psychology made by the Marxist philosopher Louis Althusser, as well as those made by his disciples in France and Latin America. It poses the possibility to restart this critique by drawing upon the Lacanian theory to the extent that, as the Althusserian theory, it is antipsychological. In a second moment, it describes the historical, economic, political, and subjective characteristics of the neoliberal metamorphosis of capitalism, and then, we identify the psychologies that appear in this context. Subsequently, it proposes a return to the althusserian reading method, namely, symptomale reading, to analyze the Positive Psychology discourse that emerges in the widespread dominance of neoliberal policies in the 21st century. Then, we read the symptoms of Positive Psychology discourse, and we identify that this psychology is constituted by neoliberal wellbeing and unlimited enjoyment imperative. This reading elucidates the ideological functions of this psychology in the neoliberal-posfordist organization of labor and its ideological effects on the subject, such as a) reflection, reinforcement, and concealment of neoliberal ideology; b) psychoeducation of the subjects; c) fetishization of capitalist exploitation; d) objectification and suppression of the subject of the unconscious; e) illusory reappropriation of surplus-enjoyment. Finally, we argue that Positive Psychology is a structural effect of neoliberal capitalism that maintains an over-determination relationship, in which it is not only determined but determining in the reproduction of the capitalist structure: what mediates between both terms of the equation is a structural causality. We conclude that the truth of psychology lies in economics and politics.

En el contexto de la creciente psicologización de la economía y la política, este trabajo propone dilucidar la relación existente entre la psicología y el capitalismo neoliberal mediante una crítica marxista y lacaniana. Este trabajo parte de la crítica de la psicología realizada por el filósofo marxista, Louis Althusser, así como las realizadas por sus discípulos en Francia y Latinoamérica. Se plantea la posibilidad de recomenzar esta crítica recurriendo a la teoría lacaniana, en la medida en que, al igual que la althusseriana, es antipsicológica. En un segundo momento, se describen las características históricas, económicas, políticas y subjetivas de la metamorfosis neoliberal del capitalismo, para luego identificar a las psicologías surgidas en tal contexto. Posteriormente, se propone un retorno al método althusseriano de lectura, a saber, la lectura sintomal, para analizar el discurso de la Psicología Positiva que surge en el dominio generalizado de las políticas neoliberales en el siglo XXI. Luego, se lee sintomalmente el discurso de la Psicología Positiva, y se identifica que esta se constituye a partir del imperativo neoliberal de bienestar y goce ilimitado. Se dilucidan las funciones ideológicas de esta psicología en la organización neoliberal-posfordista del trabajo, así como sus efectos ideológicos en el sujeto: a) reflejo, refuerzo y encubrimiento de la ideología neoliberal; b) psicoeducación de los sujetos; c) fetichización de la explotación capitalista; d) objetivación y supresión del sujeto del inconsciente; e) recuperación ilusoria del plus-de-gozar. Finalmente, se sostiene que la Psicología Positiva es un efecto estructural del capitalismo neoliberal que mantiene una relación de sobredeterminación, en la que no sólo es determinada sino determinante en la reproducción de la estructura capitalista: lo que media entre ambos términos de la ecuación es una causalidad estructural. Se concluye que la verdad de la psicología radica en la economía y en la política.
Facultad de Psicología. Maestría en Estudios Psicoanalíticos
Keywords: info:eu-repo/classification/cti/5; FP-M-2024-0451; Causalidad estructural; Neoliberalismo; Psicología crítica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18646